2015
DOI: 10.1617/s11527-015-0626-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of solution concentration, cement alkali and test duration on expansion of accelerated mortar bar test (AMBT)

Abstract: The deleterious phenomenon in concrete due to alkali-silica reactivity of an aggregate can be evaluated by an accelerated mortar bar test. This study investigates the individual and combined effect of solution concentration, cement alkali and test duration on expansion, and proposes expansion models consisted of the above-mentioned three parameters. The specimens of this study were prepared from six aggregates having different mineralogy, and three dosages of cement alkalis of 0.42, 0.84 and 1.26 % Na 2 O eq .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The results from the ASTM C1293 test confirm observations made by Islam et al [46]. They showed that the mortar bars with hematite/magnetite submerged in 1 M NaOH expanded mostly during the early state of testing up to 28 days, and the expansion rate decreased with an increase in test duration.…”
Section: Discussionsupporting
confidence: 88%
“…The results from the ASTM C1293 test confirm observations made by Islam et al [46]. They showed that the mortar bars with hematite/magnetite submerged in 1 M NaOH expanded mostly during the early state of testing up to 28 days, and the expansion rate decreased with an increase in test duration.…”
Section: Discussionsupporting
confidence: 88%
“…Similar observations have been reported in previous research. For example, Islam et al [75] studied the role of solution concentration on expansion of accelerated mortar bar test by considering three variables i.e., 0.25 N, 0.5 N, and 1.0 N solution concentration. In the case of 0.25, it was observed that mortar expansion was very low compared to identical specimens exposed to 0.5 N and 1.0 N. It was also observed that mortar bar submerged in 0.5 N solution expanded slowly with an increase in test duration; mortar bars placed in 1.0 N solution showed higher expansion during the early age of testing and after 28 days' expansion rate was reduced.…”
Section: Effect Of Solution Concentrationmentioning
confidence: 99%
“…For instance, Tosun and Felekoglu [78] observed the effect of total alka cement on expansion caused by the ASR in mortar bars containing admixtu al. [75] investigated the effect of cement alkalis on mortar bar expansion de solution concentration NaOH and test duration. A higher rate of expansion w It was also observed that the cement alkali contents had a significant influence for specimens exposed to 0.5 N and 1.5 N solution concentration.…”
Section: Effect Of Cement Alkalismentioning
confidence: 99%
See 1 more Smart Citation
“…The reactivity of the volcanic rocks comes from the interstitial material of low crystallinity: volcanic glass and/or mesostasis [14][15][16]. After characterizing the rocks selected for the study (item II), the mesostasis analysis was conducted.…”
Section: A Interstitial Matter Analysismentioning
confidence: 99%